Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Genomic analysis of Vanessa tameamea, the threatened Hawaiian endemic butterfly, reveals population genetic structure relevant to conservation efforts - Haley E. Arnold; Julian R. Dupuis; Daniel Rubinoff; William P. Haines; Michael San Jose; Renee L. Corpuz; Angela N. Kauwe; Tyler J. Simmonds; Scott M. Geib; Sheina B. Sim (Conservation Genetics, 2025)
Patterns of divergence and speciation on islands have long been of interest in the broader study of evolution. Hawaiʻi’s endemic Kamehameha butterfly ( Vanessa tameamea ) is experiencing population decline, but because of its high vagility and assumed genetic homogeneity as a species, its population structure has not been investigated. To evaluate V. tameamea genetic variation across the Hawaiian Islands, we assembled a reference quality genome assembly for the species using HiFi and HiC reads and performed range-wide population genetic analyses using ddRAD sequencing data. A discriminant analysis of principal components (DAPC) revealed that, contrary to prior assumptions, V. tameamea populations appear to be diverging based on geography, in a pattern similar to other native Hawaiian terrestrial arthropods. Specifically, through demographic history analyses, we find that the distinct population on Kauaʻi is likely to be ancestral, the central islands of Maui, Molokaʻi, and Oʻahu comprise another population, and Hawaiʻi Island forms a third population, with likely more gene exchange with the central islands. Finally, we investigate the SNPs driving differences between groups and find that many are associated with genes that may be relevant to local adaptation to environmental chemicals such as host plant defenses or chemicals introduced by human activity, notably to do with metabolism and detoxification. While much field work remains to investigate any cryptic or phenotypic patterns as well as quantify effective migration, we hope that this work will inform refinement of conservation plans for one of Hawaiʻi’s two native butterflies.

In silico analysis of balsaminol as anti-viral agents targeting SARS-CoV-2 main protease, spike receptor binding domain and papain-like protease receptors - Daniel Danladi Gaiya; Aliyu Muhammad; Joy Sim Musa; Richard Auta; Anthony John Dadah; Rachael Oluwafunmilayo Bello; Madinat Hassan; Samuel Sunday Eke; Rebecca Imoo Odihi; Musa Sankey (In Silico Pharmacology, 2024)

Highly active fish in low oxygen environments: vertical movements and behavioural responses of bigeye and yellowfin tunas to oxygen minimum zones in the eastern Pacific Ocean - Nicolas E. Humphries; Daniel W. Fuller; Kurt M. Schaefer; David W. Sims (Marine Biology, 2024)
Oxygen minimum zones in the open ocean are predicted to significantly increase in volume over the coming decades as a result of anthropogenic climatic warming. The resulting reduction in dissolved oxygen (DO) in the pelagic realm is likely to have detrimental impacts on water-breathing organisms, particularly those with higher metabolic rates, such as billfish, tunas, and sharks. However, little is known about how free-living fish respond to low DO environments, and therefore, the effect increasing OMZs will have cannot be predicted reliably. Here, we compare the responses of two active predators (bigeye tuna Thunnus obesus and yellowfin tuna Thunnus albacares ) to DO at depth throughout the eastern Pacific Ocean. Using time-series data from 267 tagged tunas (59,910 days) and 3D maps of modelled DO, we find that yellowfin tuna respond to low DO at depth by spending more time in shallower, more oxygenated waters. By contrast, bigeye tuna, which forage at deeper depths well below the thermocline, show fewer changes in their use of the water column. However, we find that bigeye tuna increased the frequency of brief upward vertical excursions they performed by four times when DO at depth was lower, but with no concomitant significant difference in temperature, suggesting that this behaviour is driven in part by the need to re-oxygenate following time spent in hypoxic waters. These findings suggest that increasing OMZs will impact the behaviour of these commercially important species, and it is therefore likely that other water-breathing predators with higher metabolic rates will face similar pressures. A more comprehensive understanding of the effect of shoaling OMZs on pelagic fish vertical habitat use, which may increase their vulnerability to surface fisheries, will be important to obtain if these effects are to be mitigated by future management actions.

The dynamic influence of subsurface geological processes on the assembly and diversification of thermophilic microbial communities in continental hydrothermal systems - Kenneth W.W. Sims; Cole M. Messa; Sean R. Scott; Andrew D. Parsekian; Andrew Miller; Abraham L. Role; Timothy P. Moloney; Everett L. Shock; Jacob B. Lowenstern; R. Blaine McCleskey; Matthew A. Charette; Bradley J. Carr; et al. (Geochimica et Cosmochimica Acta, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Tropical macrophytes promote phytoplankton community shifts in lake mesocosms: relevance for lake restoration in warm climates - Darren Z. H. Sim; Maxine A. D. Mowe; Yiluan Song; Joy Lu; Hugh T. W. Tan; Simon M. Mitrovic; Daniel L. Roelke; Darren C. J. Yeo (Hydrobiologia, 2021)

Uptake of groundwater nitrogen by a near-shore coral reef community on Bermuda - Zoe C. Sims; Anne L. Cohen; Victoria H. Luu; Xingchen T. Wang; Daniel M. Sigman (Coral Reefs, 2020)

Overhauling Ocean Spatial Planning to Improve Marine Megafauna Conservation - Ana Micaela Martins Sequeira; Graeme Clive Hays; David W. Sims; Víctor M. Eguíluz; Jorge P. Rodríguez; Michelle R. Heupel; Rob Harcourt; Hannah Calich; Nuno Queiroz; Daniel Paul Costa; Juan Fernández-Gracia; Luciana C. Ferreira; et al. (Frontiers in Marine Science, 2019)

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Transpacific coalescent pathways of coconut rhinoceros beetle biotypes: Resistance to biological control catalyses resurgence of an old pest - Jonathan Bradley Reil; Camiel Doorenweerd; Michael San Jose; Sheina B. Sim; Scott M. Geib; Daniel Rubinoff (Molecular Ecology, 2018)
Biological control agents have several advantages over chemical control for pest management, including the capability to restore ecosystem balance with minimal non‐target effects and a lower propensity for targets to develop resistance. These factors are particularly important for invasive species control. The coconut rhinoceros beetle ( Oryctes rhinoceros Linnaeus) is a major palm pest that invaded many Pacific islands in the early 20th century through human‐mediated dispersal. Application of the Oryctes nudivirus in the 1960s successfully halted the beetle's first invasion wave and made it a textbook example of successful biological control. However, a recently discovered O. rhinoceros biotype that is resistant to the nudivirus appears to be correlated with a new invasion wave. We performed a population genomics analysis of 172 O. rhinoceros from seven regions, including native and invasive populations, to reconstruct invasion pathways and explore correlation between recent invasions and biotypes. With dd RAD sequencing, we generated data sets ranging from 4,000 to 209,000 loci using stacks and ipyrad software pipelines and compared genetic signal in downstream clustering and phylogenetic analyses. Analysis suggests that the O. rhinoceros resurgence is mediated by the nudivirus‐resistant biotype. Genomic data have been proven essential to understanding the new O. rhinoceros biotype's invasion patterns and interactions with the original biotype. Such information is crucial to optimization of strategies for quarantine and control of resurgent pests. Our results demonstrate that while invasions are relatively rare events, new introductions can have significant ecological consequences, and quarantine vigilance is required even in previously invaded areas.

Population genomics and comparisons of selective signatures in two invasions of melon fly, Bactrocera cucurbitae (Diptera: Tephritidae) - Julian R. Dupuis; Sheina B. Sim; Michael San Jose; Luc Leblanc; M. Aftab Hoassain; Daniel Rubinoff; Scott M. Geib (Biological Invasions, 2018)

Coinfection with multiple strains of bovine papular stomatitis virus - Tao Huang; Edan R. Tulman; Diego G. Diel; Sushil Khatiwada; Will Sims; John F. Edwards; Xintian Wen; Gerald F. Kutish; Daniel L. Rock; Gustavo Delhon (Archives of Virology, 2015)

An improved approach for remotely sensing water stress impacts on forest C uptake - Daniel A. Sims; Edward R. Brzostek; Abdullah F. Rahman; Danilo Dragoni; Richard P. Phillips (Global Change Biology, 2014)
Given that forests represent the primary terrestrial sink for atmospheric CO 2 , projections of future carbon (C) storage hinge on forest responses to climate variation. Models of gross primary production ( GPP ) responses to water stress are commonly based on remotely sensed changes in canopy ‘greenness’ (e.g., normalized difference vegetation index; NDVI ). However, many forests have low spectral sensitivity to water stress ( SSWS ) – defined here as drought‐induced decline in GPP without a change in greenness. Current satellite‐derived estimates of GPP use a vapor pressure deficit ( VPD ) scalar to account for the low SWSS of forests, but fail to capture their responses to water stress. Our objectives were to characterize differences in SSWS among forested and nonforested ecosystems, and to develop an improved framework for predicting the impacts of water stress on GPP in forests with low SSWS . First, we paired two independent drought indices with NDVI data for the conterminous US from 2000 to 2011, and examined the relationship between water stress and NDVI . We found that forests had lower SSWS than nonforests regardless of drought index or duration. We then compared satellite‐derived estimates of GPP with eddy‐covariance observations of GPP in two deciduous broadleaf forests with low SSWS : the Missouri Ozark ( MO ) and Morgan Monroe State Forest ( MMSF ) AmeriFlux sites. Model estimates of GPP that used VPD scalars were poorly correlated with observations of GPP at MO ( r 2 = 0.09) and MMSF ( r 2 = 0.38). When we included the NDVI responses to water stress of adjacent ecosystems with high SSWS into a model based solely on temperature and greenness, we substantially improved predictions of GPP at MO ( r 2 = 0.83) and for a severe drought year at the MMSF ( r 2 = 0.82). Collectively, our results suggest that large‐scale estimates of GPP that capture variation in SSWS among ecosystems could improve predictions of C uptake by forests under drought.

Chronic water stress reduces tree growth and the carbon sink of deciduous hardwood forests - Edward R. Brzostek; Danilo Dragoni; Hans Peter Schmid; Abdullah F. Rahman; Daniel Sims; Craig A. Wayson; Daniel J. Johnson; Richard P. Phillips (Global Change Biology, 2014)
Predicted decreases in water availability across the temperate forest biome have the potential to offset gains in carbon (C) uptake from phenology trends, rising atmospheric CO 2 , and nitrogen deposition. While it is well established that severe droughts reduce the C sink of forests by inducing tree mortality, the impacts of mild but chronic water stress on forest phenology and physiology are largely unknown. We quantified the C consequences of chronic water stress using a 13‐year record of tree growth ( n = 200 trees), soil moisture, and ecosystem C balance at the Morgan–Monroe State Forest ( MMSF ) in Indiana, and a regional 11‐year record of tree growth ( n > 300 000 trees) and water availability for the 20 most dominant deciduous broadleaf tree species across the eastern and midwestern USA . We show that despite ~26 more days of C assimilation by trees at the MMSF , increasing water stress decreased the number of days of wood production by ~42 days over the same period, reducing the annual accrual of C in woody biomass by 41%. Across the deciduous forest region, water stress induced similar declines in tree growth, particularly for water‐demanding ‘mesophytic’ tree species. Given the current replacement of water‐stress adapted ‘xerophytic’ tree species by mesophytic tree species, we estimate that chronic water stress has the potential to decrease the C sink of deciduous forests by up to 17% (0.04 Pg C yr −1 ) in the coming decades. This reduction in the C sink due to mesophication and chronic water stress is equivalent to an additional 1–3 days of global C emissions from fossil fuel burning each year. Collectively, our results indicate that regional declines in water availability may offset the growth‐enhancing effects of other global changes and reduce the extent to which forests ameliorate climate warming.

Isotopic assessment of CO2 production through soil organic matter decomposition in the tropics - Shingo Ueda; Chun-Sim U. Go; Shigehiro Ishizuka; Haruo Tsuruta; Anas Iswandi; Daniel Murdiyarso (Nutrient Cycling in Agroecosystems, 2005)

Canopy radiation‐ and water‐use efficiencies as affected by elevated [CO 2 ] - Dafeng Hui; Yiqi Luo; Weixin Cheng; J. S. Coleman; Dale W. Johnson; Daniel A. Sims (Global Change Biology, 2001)
Summary This study used an environmentally controlled plant growth facility, EcoCELLs, to measure canopy gas exchanges directly and to examine the effects of elevated [CO 2 ] on canopy radiation‐ and water‐use efficiencies. Sunflowers ( Helianthus annus var. Mammoth) were grown at ambient (399 μmol mol −1 ) and elevated [CO 2 ] (746 μmol mol −1 ) for 53 days in EcoCELLs. Whole canopy carbon‐ and water‐fluxes were measured continuously during the period of the experiment. The results indicated that elevated [CO 2 ] enhanced daily total canopy carbon‐ and water‐fluxes by 53% and 11%, respectively, on a ground‐area basis, resulting in a 54% increase in radiation‐use efficiency (RUE) based on intercepted photosynthetic active radiation and a 26% increase in water‐use efficiency (WUE) by the end of the experiment. Canopy carbon‐ and water‐fluxes at both CO 2 treatments varied with canopy development. They were small at 22 days after planting (DAP) and gradually increased to the maxima at 46 DAP. When canopy carbon‐ and water‐fluxes were expressed on a leaf‐area basis, no effect of CO 2 was found for canopy water‐flux while elevated [CO 2 ] still enhanced canopy carbon‐flux by 29%, on average. Night‐time canopy carbon‐flux was 32% higher at elevated than at ambient [CO 2 ]. In addition, RUE and WUE displayed strong diurnal variations, high at noon and low in the morning or afternoon for WUE but opposite for RUE. This study provided direct evidence that plant canopy may consume more, instead of less, water but utilize both water and radiation more efficiently at elevated than at ambient [CO 2 ], at least during the exponential growth period as illustrated in this experiment.

Photosynthesis, respiration, and net primary production of sunflower stands in ambient and elevated atmospheric CO 2 concentrations: an invariant NPP:GPP ratio? - Weixin Cheng; Daniel A. Sims; Yiqi Luo; James S. Coleman; Dale W. Johnson (Global Change Biology, 2000)
Summary The effect of elevated CO 2 on photosynthesis, respiration, and growth efficiency of sunflower plants at the whole‐stand level was investigated using a whole‐system gas exchange facility (the EcoCELLs at the Desert Research Institute) and a 13 C natural tracer method. Total daily photosynthesis (GPP), net primary production (NPP), and respiration under the elevated CO 2 treatment were consistently higher than under the ambient CO 2 treatment. The overall level of enhancement due to elevated CO 2 was consistent with published results for a typical C3 plant species. The patterns of daily GPP and NPP through time approximated logistic curves under both CO 2 treatments. Regression analysis indicated that both the rate of increase (the parameter ‘ r ’) and the maximum value (the parameter ‘ k ’) of daily GPP and NPP under the elevated CO 2 treatment were significantly higher than under the ambient CO 2 treatment. The percentage increase in daily GPP due to elevated CO 2 varied systematically through time according to the logistic equations used for the two treatments. The GPP increase due to elevated CO 2 ranged from approximately 10% initially to 73% at the peak, while declining to about 33%, as predicted by the ratio of the two maximum values. Different values of percentage increase in GPP and NPP were obtained at different sampling times. This result demonstrated that one‐time measurements of percentage increases due to elevated CO 2 could be misleading, thereby making interpretation difficult. Although rhizosphere respiration was substantially enhanced by elevated CO 2 , no effect of elevated CO 2 on R:P (respiration:photosynthesis) was found, suggesting an invariant NPP:GPP ratio during the entire experiment. Further validation of the notion of an invariant NPP:GPP ratio may significantly simplify the process of quantifying terrestrial carbon sequestration by directly relating total photosynthesis to net primary production.

Carbon budgeting in plant–soil mesocosms under elevated CO 2 : locally missing carbon? - Weixin Cheng; Daniel A. Sims; Yiqi Luo; Dale W. Johnson; J. Timothy Ball; James S. Coleman (Global Change Biology, 2000)
Summary Studies have suggested that more carbon is fixed due to a large increase in photosynthesis in plant–soil systems exposed to elevated CO 2 than could subsequently be found in plant biomass and soils –‐ the locally missing carbon phenomenon. To further understand this phenomenon, an experiment was carried out using EcoCELLs which are open‐flow, mass‐balance systems at the mesocosm scale. Naturally occurring 13 C tracers were also used to separately measure plant‐derived carbon and soil‐derived carbon. The experiment included two EcoCELLs, one under ambient atmospheric CO 2 and the other under elevated CO 2 (ambient plus 350 μL L − 1 ). By matching carbon fluxes with carbon pools, the issue of locally missing carbon was investigated. Flux‐based net primary production ( NPP f ) was similar to pool‐based primary production ( NPP p ) under ambient CO 2 , and the discrepancy between the two carbon budgets (12 g C m − 2 , or 4% of NPP f ) was less than measurement errors. Therefore, virtually all carbon entering the system under ambient CO 2 was accounted for at the end of the experiment. Under elevated CO 2 , however, the amount of NPP f was much higher than NPP p , resulting in missing carbon of approximately 80 g C m − 2 or 19% of NPP f which was much higher than measurement errors. This was additional to the 96% increase in rhizosphere respiration and the 50% increase in root growth, two important components of locally missing carbon. The mystery of locally missing carbon under elevated CO 2 remains to be further investigated. Volatile organic carbon, carbon loss due to root washing, and measurement errors are discussed as some of the potential contributing factors.

Nonlinearity of photosynthetic responses to growth in rising atmospheric CO 2 : an experimental and modelling study - YiqI. Luo; Daniel A. Sims; Kevin L. Griffin (Global Change Biology, 1998)
Nonlinear responses of photosynthesis to the CO 2 concentration at which plants were grown (C g ) have been often reported in the literature. This study was designed to develop mechanistic understanding of the nonlinear responses with both experimental and modelling approaches. Soybean (Glycine max) was grown in five levels of C g (280, 350, 525, 700, 1000 ppm) with either a high or low rate of nitrogen fertilization. When the rate of nitrogen fertilization was high, the photosynthetic rate measured at C g was highest in plants from the 700 ppm CO 2 treatment. When the rate of nitrogen fertilization was low, little variation was observed in the photosynthetic rates of plants from the different treatments measured at their respective C g . Measurements of CO 2 ‐induced changes in mass‐based leaf nitrogen concentration (n m , an index of changes in biochemical processes) and leaf mass per unit area (h, an index of morphological properties) were used in a model and indicate that the nonlinearity of photosynthetic responses to C g is largely determined by relative changes in photosynthetic sensitivity, biochemical downregulation, and morphological upregulation. In order to further understand the nonlinear responses, we compiled data from the literature on CO 2 ‐induced changes in n m and h. These compiled data indicate that h generally increases and n m usually decreases with increasing C g , but that the trajectories and magnitudes of the changes in h and n m vary with species and growth environments. Integration of these variables (n m and h) into a biochemically based model of photosynthesis enabled us to predict diverse responses of photosynthesis to C g . Thus a general mechanism is suggested for the highly variable, nonlinear responses of photosynthesis to C g reported in the literature.